The quick fix : why fad psychology can't cure our social ills - Singal, Jesse, 1983- (New York : Farrar, Straus and Giroux, 2021)
"How popular psychology fails to solve problems facing society and draws attention and resources away from more effective structural fixes"--
Includes bibliographical references and index.
HB
Keywords: Psychology -- Popular works; Human behavior; Social problems; Psychology